Supplier Development framework analysis in South Africa's upstream oil & gas sector - Peinke, Laura (Research of GSB, 2018)
Although considerable attention has been given to the prospects for developing small, medium and micro-enterprises, and more specifically local content, very little relevant research has been undertaken in South Africa's upstream oil and gas industry with specific reference to an offshore supply base. In this research report, findings have been presented from 15 detailed interviews conducted with Transnational Corporations, local SMEs, government departments, industry associations, small business support organisations, and international respondents involved in supplier development programmes within the Oil & Gas sector. The aim of the research was to investigate the difficulties that confront local small businesses, and examine opportunities for outsourcing services to SMEs and encouraging development of business linkages in South Africa's upstream oil and gas industry. The South African research has been conducted within the context of existing international research on upstream oil and gas supplier development, and small enterprise development in developing countries.